Highly flexible graphene nanoplatelet-polydimethylsiloxane strain sensors with proximity-sensing capability. (27th April 2020) - Lee, Hyokeun; Kim, Min Jung; Kim, Jong Hun; Lee, Jong-Young; Ji, Eunji; Capasso, Andrea; Choi, Heon-Jin; Shim, Wooyoung; Lee, Gwan-Hyoung
Abstract: Flexible strain sensors are essential for providing electronic skin with the ability to detect motions and pressure, enabling their use in health applications and robotics. In this context, strain sensors should simultaneously guarantee a high sensitivity and flexibility, with a fast response when applied to the detection of various human motions. Here, we demonstrate a flexible strain sensor made of graphene nanoplatelets encapsulated between two elastomer films with a high sensitivity and stretchability. The liquid-exfoliated graphene nanoplatelets were spray-coated on the first elastomer film and then encapsulated by the second elastomer film. The encapsulated graphene sensor exhibited a high gauge factor, fast responsivity, and high durability. It proved stretchable up to 290% and highly bendable (operating at almost zero bending radius). As an additional key feature, proximity sensing to detect remote motions of a distant object was demonstrated, owing to the unique characteristic of graphene, i.e., variations in its electrostatic in response to the interaction between the surface charges of the elastomer and the electrostatic charges of the remote object. Our work introduces a novel route for the fabrication of flexible graphene sensors with proximity-sensing capability, which are useful for wearable smart devices and human motion detection.